(untitled) (The Review of Diabetic Studies, 2024)
Background: Digital and technological innovations have revolutionized infection control, addressing the ongoing global burden of healthcare-associated infections (HAIs) and the urgent need for more efficient, scalable, and accurate prevention strategies. These advancements have shifted practice from traditional manual surveillance, which is labor-intensive and potentially error-prone, towards automated systems leveraging artificial intelligence (AI), machine learning (ML), electronic health records (EHRs), and real-time monitoring platforms.​ Methods: A systematic review was conducted to evaluate studies published from 2018 onward, focusing on digital solutions including AI-driven surveillance, mobile health applications, Internet of Medical Things (IoMT), wearable technologies, blockchain, and automated disinfection. The methodology emphasized synthesis of clinical evidence on efficacy, implementation challenges, and clinical outcomes, with inclusion criteria targeting hospital and long-term care settings and prioritizing peer-reviewed, real-world deployments.​ Results: Evidence indicates that digital surveillance systems, AI models, and IoMT platforms offer superior sensitivity, specificity, and timeliness in HAI detection versus manual methods. Automated disinfection technologies and wearable devices support proactive environmental and patient monitoring, collectively reducing infection rates and relevant surrogate markers. Adoption is challenged by infrastructural, interoperability, cost, and workforce readiness barriers, while privacy, regulatory, and ethical issues remain significant considerations.​ Conclusions: The integration of advanced digital technologies has led to measurable improvements in infection control efficacy, patient safety, and workflow efficiency. Continued real-world validation, interdisciplinary collaboration, and ethical frameworks are necessary to maximize implementation and overcome persistent barriers, positioning these innovations as essential tools in future infection control strategies.​